Chronic limping in childhood, what else other than juvenile idiopathic arthritis: a case series - Cristina Tumminelli; Serena Pastore; Andrea Taddio (BMC, 2023)
Abstract Background Limping is a common clinical symptom in childhood; different clinical conditions may lead to limping and the diagnosis of the underlying cause may often be a challenge for the pediatrician. Case presentation We describe the clinical manifestations, radiological pictures and disease course of other causes of limping in childhood, through a case series of seven cases and a brief discussion of each disease. Conclusions although trauma is the most common cause of acute limping, when there is no history of traumatic events and the limping has a chronic course, Juvenile Idiopathic Arthritis is usually the most likely clinical diagnosis. However, other some rare conditions should be taken into account if JIA is not confirmed or if it presents with atypical clinical picture.